The EU decarbonisation roadmap 2050: What way to walk? - Michael Hübler; Andreas Löschel (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2012)
We carry out a detailed CGE (Computable General Equilibrium) analysis of the EU Decarbonisation Roadmap 2050 on a macroeconomic and on a sectoral level. Herein, we study a Reference scenario that implements existing EU policies as well as 3 unilateral and 3 global climate action scenarios. We identify global climate action with international emissions trading and the ful l equalization of CO2 prices across all (EU) sectors as a reasonable policy option to avoid additional costs of the Decarbonisation Roadmap to a large extent. This policy option may include CDM (Clean Development Mechanism in the sense of 'where'-flexibility) in an extended form if there are countries without emissions caps. Moreover, we identify diverse sectoral effects in terms of output, investment, emissions and international competitiveness. We conclude that the successful realization of the EU Decarbonisation Roadmap probably requires a wise and joint consideration of technology, policy design and sectoral aspects.
Keywords: C68; F18; Q43; Q54; 330; EU; Decarbonisation Roadmap; Copenhagen Pledges; post Kyoto; energy-intensive sectors; competitiveness; leakage